Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/1522-2683(200209)23:17<3027::aid-elps3027>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Comparative enantioseparations with native β-cyclodextrin and heptakis-(2-O-methyl- 3,6-di-O-sulfo)-β-cyclodextrin in capillary electrophoresis

Abstract: Twenty-three cationic chiral analytes were resolved in capillary electrophoresis using native beta-cyclodextrin and single isomer heptakis-(2-O-methyl-3,6-di-O-sulfo)-beta-cyclodextrin as chiral selectors. For 12 of 16 chiral analytes resolved with both chiral selectors the enantiomer migration order was opposite. In selected cases the structure of cyclodextrin-analyte complexes in aqueous solution was investigated using one-dimensional transverse rotating frame nuclear Overhauser and exchange spectroscopy. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…In the case of derivatized CDs additional interactions such as ionic interactions for CDs bearing charged substitutents have to be considered as well. In fact it has been demonstrated that the formation of an inclusion complex is not a prerequisite for the stereospecific recognition of analyte enantiomers by a CD [42,43]. Within the many techniques applied to study the structures of CD-analyte complexes NMR has significantly contributed [44][45][46].…”
Section: Chiral Separations Mechanisms In Capillary Electrophoresismentioning
confidence: 99%
“…In the case of derivatized CDs additional interactions such as ionic interactions for CDs bearing charged substitutents have to be considered as well. In fact it has been demonstrated that the formation of an inclusion complex is not a prerequisite for the stereospecific recognition of analyte enantiomers by a CD [42,43]. Within the many techniques applied to study the structures of CD-analyte complexes NMR has significantly contributed [44][45][46].…”
Section: Chiral Separations Mechanisms In Capillary Electrophoresismentioning
confidence: 99%
“…This additional complex forming possibility may explain the higher stability of the Looking for the structural and chemical reasons of the enantiomer migration order (EMO) i.e., finding the relationships between the structure of a chiral selector, chiral analyte and analyte-selector complex on the one hand, and the EMO on the other hand, may provide important information regarding the nature of intermolecular forces involved in complex formation and enantioselective recognition of analytes by chiral selectors. In the literature several examples were reported on information regarding the involvement of different parts of an analyte in the intermolecular complex formation with CDs [25][26][27]34,35,47,48]. These data may explain the change of molecular recognition of the analytes.…”
Section: D Roesy Nmr Studiesmentioning
confidence: 99%
“…Chankvetadze et al [60] observed opposite enantiomer migration order for 12 out of 16 basic analytes separated by b-CD and heptakis-…”
Section: Separation Of Drug Enantiomersmentioning
confidence: 99%